Laser heating effect on Raman analysis of CO2 co-existing as liquid and vapor in olivine-hosted melt inclusion bubbles - DeVitre, Charlotte L.; Dayton, Kyle; Gazel, Esteban; Pamukçu, Ayla; Gaetani, Glenn; Wieser, Penny E. (Volcanica, 2023)
Raman spectroscopy has become the tool of choice for analyzing fluid inclusions and melt inclusion (MI) vapor bubbles as it allows the density of CO2-rich fluids to be quantified. Measurements are often made at ambient temperature (Tamb 18-25 °C), resulting in reported bulk densities between 0.2 and 0.7 g/mL despite that single-phase CO2 under these conditions is thermodynamically unstable and instead consists of a liquid ( 0.7 g/mL), and a vapor phase ( 0.2 g/mL). Here, we present results from experiments conducted at Tamb and 37 °C (above the CO2 critical temperature) on 14 natural CO2-rich MI bubbles from Mount Morning, Antarctica. Here, we show that at Tamb, laser power strongly affects the CO2 Raman spectrum of MI bubbles with bulk densities within the miscibility gap. High-power laser heating and low spectral resolution explain why published measurements have reported such bulk densities at Tamb even when using an instrument-specific calibration.